2003
DOI: 10.1034/j.1600-0501.2003.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Representative marketing‐oriented study on implants in the Austrian population. II. Implant acceptance, patient‐perceived cost and patient satisfaction

Abstract: Oral implantology is an established subspecialty of restorative dental and oral surgery. While an extensive body of evidence on the fundamentals of osseointegration and associated factors has been published, marketing-oriented analyses based on representative public opinion polls of implant acceptance, patient-perceived cost and patient satisfaction are scarce. In this study, an attempt was made to address these points by questioning a representative sample of 1000 adults in the household setting. The intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 16 publications
8
69
2
1
Order By: Relevance
“…According to a study by Tepper et al 17 costs were one of the most important factors for not choosing dental replacement, especially for implant treatment option, which somehow is similar to the findings of present study. The majority of the participants reported the source of information regarding the various options for the replacement of missing teeth came directly from the dentist (70%) as compared with other sources (37%), such as Internet and mass media.…”
Section: Jcdpsupporting
confidence: 81%
“…According to a study by Tepper et al 17 costs were one of the most important factors for not choosing dental replacement, especially for implant treatment option, which somehow is similar to the findings of present study. The majority of the participants reported the source of information regarding the various options for the replacement of missing teeth came directly from the dentist (70%) as compared with other sources (37%), such as Internet and mass media.…”
Section: Jcdpsupporting
confidence: 81%
“…Treatment costs and comparative economic analyses are increasingly the subjects of discussion in the dental literature. [17][18][19][20][21] Pjetursson et al 8 reported in his study that the costs associated with implant therapy in Switzerland were considered to be justified, while Tepper et al 30 described the implantsupported rehabilitation to be very expensive in Austria. The goals of our study were to investigate patients' assessments of and satisfaction with the treatment outcomes and to consider the cost-effectiveness of the applied treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Cost of treatment seemed to be the most deciding factor in majority. In a study conducted by [20] . to assess implant acceptance, patient perceived cost and patient satisfaction in Austrian population, it was observed that interest in implants increases with increase in family income.…”
Section: Discussionmentioning
confidence: 99%